2017
DOI: 10.1097/tp.0000000000001322
|View full text |Cite
|
Sign up to set email alerts
|

Donor-Transmitted Atherosclerosis Associated With Worsening Cardiac Allograft Vasculopathy After Heart Transplantation

Abstract: BackgroundThe influence of preexisting donor-transmitted atherosclerosis (DA) on cardiac allograft vasculopathy (CAV) development remains unclear.MethodsWe performed 3-dimensional intravascular ultrasound (3D-IVUS) analysis in 42 heart transplantation (HTx) recipients at 2.1 ± 0.9 months (baseline) and 12.2 ± 0.4 months post-HTx, as well as consecutive 3D-IVUS analyses up to 3 years post-HTx in 35 of the 42 recipients. Donor-transmitted atherosclerosis was defined as a maximal intimal thickness of 0.5 mm or gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 35 publications
2
20
2
Order By: Relevance
“…Donor age, when analyzed, is consistently reported to be associated with CAV detection []. This concept is not novel and is mainly related to the risk of transmission of donor coronary lesions to the recipient, as also suggested by studies finding that male donors – more likely to bear subclinical coronary lesions – may be associated with CAV development .…”
Section: Discussionmentioning
confidence: 99%
“…Donor age, when analyzed, is consistently reported to be associated with CAV detection []. This concept is not novel and is mainly related to the risk of transmission of donor coronary lesions to the recipient, as also suggested by studies finding that male donors – more likely to bear subclinical coronary lesions – may be associated with CAV development .…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, many pediatric centers reported much lower age cutoffs for adolescent recipients. While extension of this age cutoff may be warranted, concerns about the possibility of donor transmitted atherosclerosis and the potential association with allograft vasculopathy may continue to dissuade utilization of these organs in pediatric recipients.…”
Section: Discussionmentioning
confidence: 99%
“…Even though survival was not affected by donor age in the present study, we found high donor age to be a significant risk factor for CAV development. 24 Furthermore, patients with CAV are often switched to everolimus-based immunosuppression and may be subjected to closer graft function, rejection, and HLA antibody monitoring than patients without CAV. [21][22][23] According to the ISHLT registry, CAV affects 8% of survivors within the first year, 30% within 5 years, and 50% within 10 years after HTx.…”
Section: Discussionmentioning
confidence: 99%
“…The latter is known to have a different impact on prognosis than true CAV. 24 Furthermore, patients with CAV are often switched to everolimus-based immunosuppression and may be subjected to closer graft function, rejection, and HLA antibody monitoring than patients without CAV. These are all factors that could explain our findings.…”
Section: Discussionmentioning
confidence: 99%